CONTRASTIVE ANALYSIS BETWEEN ENGLIS AND INDONESIAN BASIC SENTENCE PATTERN - Sarumaha, Yunes (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
Every language has is own pattern such as English langauge and Indonesian language. This research was aimed to analyze the similarities and differences between English and Indonesian basic sentence pattern in short story of Cinderella’s. This research was designed by using qualitative research. In analyzing the data, the researcher used theory of Miles and Huberman: data reduction, data display,and conclusion drawing/verification. The result of this study showed that there were the similarities between English and Indonesian basic sentence pattern in short story of Cinderella’s. They are SVO/SPO, SV/SP, SVOC/SPOPel, SVOA/SPOKet, SVA/SPKet. Beside that, there were the differences between English and Indonesian basic sentence pattern in short story of Cinderella’s are SVC/SPel, SVV/SP, SVC/SPKet. It is suggested to the English teacher to pay much attention to the similarities and differences between English and Indonesian basic sentence pattern to help the students understand about basic sentence pattern easly.